PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GENIALLY PADA MATA PELAJARAN DASAR-DASAR MANAJEMEN PERKANTORAN DAN LAYANAN BISNIS - Zahna Ashanti Trisnantya; Marsofiyati; Ervina Maulida (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning in the Basics of Office Management and Business Services course is still dominated by the lecture method and simple PowerPoint media, resulting in a lack of interactivity. This study aims to develop Genially-based interactive learning media on the topic of Job Profile, as well as to determine its feasibility according to material and media experts and student responses. The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observation, questionnaires, and documentation, then analyzed using quantitative descriptive analysis with a five-point Likert scale. The results showed a feasibility level of 100% from material experts and 88% from media experts (very feasible category). Student responses showed highly practical results, namely 98% in the one-to-one trial, 95.6% in the small group trial, and 93.1% in the large group trial. Thus, the Genially-based interactive learning media is declared very feasible for use by tenth-grade Logistics Management students at SMK Negeri 8 Jakarta.